Green CSR Moderated by Public Visibility and Innovation Performance at Indonesia Companies - Farah Margaretha Leon, Rahmat Hidayat, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
This study aims to analyze the green CSR Ã‚Â of innovation performance Ã‚Â with firms approval variables Ã‚Â and public visibility Ã‚Â Ã‚Â can support moderating the relationship of green CSR Ã‚Â and innovation. The research sample was 33 manufacturing companies. The results showed that the Ã‚Â green CSR has a positive and significant effect on innovation . Also, the company approval variable has been proven to moderate the direction of a positive relationship between green CSR and innovation . The results also prove that public visibility is proven to moderate the direction of the negative relationship between green CSR and performance. This study provide information that shows great concern for the environment; it will increase the company in making changes through innovation activities. Also, the higher the company's approval and public visibility, the company will get support from various stakeholders to run the firms. The level of company concern for CSR activities will be a misjudgment for investors.